Construction Research Congress 2014 2014
DOI: 10.1061/9780784413517.177
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Project Delivery Methods for Water and Wastewater Projects: The Satisfaction Level of Owners

Abstract: According to the 2013 Report Card for America's Infrastructure, prepared by American Society of Civil Engineers (ASCE), the drinking water and wastewater infrastructure received grade of 'D'. The American Water Works Association (AWWA) estimated that it would cost about $1 trillion to replace every drinking water pipe in U.S. Further, it would cost about $298 billion over the next 20 years to fix the nation's wastewater and storm water systems. Owners, engineers, and contractors are using alternative project d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…WDBC has been conducting satisfaction level surveys of APD use in water and wastewater since 2009. In 2012, WDBC found that US municipal owners were very satisfied with the APD method used in their water and wastewater projects (Shrestha et al , 2014). About 159 respondents responded the survey, and it was found that the highest satisfaction levels the municipal owners had were related to the level of the owner's involvement in the design process, the quality of the completed projects and the contractors' communication process with the owners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…WDBC has been conducting satisfaction level surveys of APD use in water and wastewater since 2009. In 2012, WDBC found that US municipal owners were very satisfied with the APD method used in their water and wastewater projects (Shrestha et al , 2014). About 159 respondents responded the survey, and it was found that the highest satisfaction levels the municipal owners had were related to the level of the owner's involvement in the design process, the quality of the completed projects and the contractors' communication process with the owners.…”
Section: Literature Reviewmentioning
confidence: 99%